THE DEVELOPMENT AND VALIDATION OF ANALYTICAL METHOD FOR EVALUATING GALLIC ACID IN ETHYL ACETATE FRACTION (EAF) OF SNEDDS FORMULATION: QUANTITATIVE ANALYSIS WITH IN VITRO ASSAY - APRIDAMAYANTI, PRATIWI; PRATIWI, LIZA; SARI, RAFIKA (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aimed to develop a simple, accurate, precise, sensitive, robust, and stable analytical method for the evaluation of gallic acid in Self-Nanoemulsifying Drug Delivery System (SNEDDS) incorporating ethyl acetate fraction (EAF) of Melastoma malabathricum leaves in combination with Gentamicin. Methods: Validation process followed ICH guidelines and applied a reverse phase HPLC method with a mobile phase of acetonitrile-phosphoric buffer at pH 3.03 (20:80 v/v). The stationary phase consisted of a VP-ODS shim-pack C-18 column (250x4.6 mm) with a flow rate of 0.2 ml/min and detection at 263 nm using an Ultraviolet detector. Additionally, antioxidant activity was assessed through the DPPH and FRAP methods, and SPF value was determined with a UV/Vis spectrophotometer in the 290-390 nm wavelength range. Results: The results showed that the retention time of quercetin was 16.648 min with a tailing factor of 1.623. The regression equation (y=224689x-989000) had a concentration range of 10-55 µg/ml and a correlation value of 0.9920. Limit of Detection (LOD) and Limit of Quantification (LOQ) were found to be 2.394±0.086 and 7.254±0.260 µg/ml, respectively. Method accuracy, determined by recovery values at concentrations of 50%, 100%, and 150%, ranged from 91.18% to 109.49%. Repeatability inter-day variations were expressed as %RSD values of 1.027-1.963% for AUC and 0.150-0.145 for RT. Moreover, the applied method showed stability within a temperature range of 14 °C–35 °C. Analysis showed gallic acid content of 1.773±0.049 mg/g in SNEDDS EAF formulation. Antioxidant activity measured through the DPPH and FRAP methods yielded IC50 values of 4.167±0.552 µg/ml and 20.253±0.619 µg/ml, respectively, while SPF value at SNEDDS concentration of 150 µg/ml was 36.993±0.183. Conclusion: This study successfully developed a precise, accurate, specific, and stable method for quantifying gallic acid levels in SNEDDS EAF of Melastoma malabathricum leaves in combination with Gentamicin. Therefore, SNEDDS EAF formulation exhibited an effective wound-healing potential, supported by a robust quality control process.